Expression of Pannexin3 in human odontoblast-like cells and its hemichannel function in mediating ATP release. Issue 10 (October 2015) - Fu, Dongjie; Song, Fangfang; Sun, Hualing; Pei, Dandan; Wang, Yake; Lei, Jinmei; Huang, Cui
Highlights Pannexin3 mRNA and protein are detected in the human dental pulp tissue and hOBs. To examine the function of Panx3, Panx3 over expression and knockdown hOBs were established. In presence of cold stimulus, ATP was released from hOBs into extracellular space. Panx3 hemichannel is one of the major ATP release channels in hOBs.